Mucuna pruriens Treatment for Parkinson Disease: A Systematic Review of Clinical Trials - Fatima Hammoud; Ali Ismail; Reem Zaher; Rania El Majzoub; Linda Abou-Abbas (Parkinson's Disease)
Conclusion: M. pruriens shows promise in improving motor symptoms and reducing therapy complications in PD patients. However, current clinical evidence is limited, and further high-quality trials are needed to confirm its efficacy and safety.